SAND MINING, LAND DEGRADATION AND CONFLICT MANAGEMENT IN EVBUOBANOSA, EDO STATE,NIGERIA (2023)
Sand Mining (SM) is the extraction of sand aggregate from land surface and water bodies. Globally, sand is a critical resource for construction purposes. In Nigeria, SM is a process that degenerates into land degradation and conflict involving a network of people and structures. Extant studies have focused more on sand extraction and environmental degradation than its associated structures and conflicts. This study, therefore, examined land degradation and conflict management due to SM, with a view to determining the extent of SM, the structural organisations involved, livelihood implications of resultant land degradation, the networks of associated conflict and the conflict management mechanisms in Evbuobanosa Dukedom, Edo State, Nigeria. Theory of Ecological Marxism guided the study, while the exploratory design was adopted. Qualitative data were purposively collected from Abudu, Evbuobanosa and Iru communities. Secondary data were sourced from the records of Federal Ministry of Mines and Steel, Benin-city office. Key Informant Interviews were conducted with 10 community leaders, six youth leaders, four pit owners and four environmental management experts. In-depth interviews were conducted with 40 sand miners, four SM association leaders, six tipper drivers, 18 farmers and eight fishermen. Eighteen Focus Group Discussion sessions were held with sand miners (9), farmers (4) and community members (5). Two case studies were also conducted with sand miners. Data were content-analysed. Sand was mined extensively, legally and illegally. Most mining sites (81.4%) were illegal with depth of 1-3 meters, each covering about 1011m2 and mined until stopped by regulators. Illegal miners thereafter, moved elsewhere to continue mining. Legal mines had depths ranging from 25-34 meters covering between 1011m2-32,374m2 and could reach down to the water table. The structural organisation of SM included the positional elites: community elders and legal miners, and artisanal working-class, illegal miners, mine workers, tipper loaders and drivers. Legal miners had renewable five-year mining permits. Site operations were largely mechanised and performed by three principal workers: manager, cashier and machine operators under close monitoring of legal miners to forestall fraud. Illegal mining was executed manually, on land and in water with slightly differing structures. On land, sand scouts/encroachers, loaders and drivers were involved, while diver-excavator, jerker (sand shoveler from canoe to beach), tipper drivers and loaders were involved in water excavation. Sand mining exacerbated flooding and induced landslides with devastating impact on the farmers. The SM drove aquatic lives out of the reach of fishermen. Legal and illegal miners clashed over sites and with indigenes. The conflict networks included guilds, kins, and fraternities: Asigidi, Osokpikan, Ogboni, Vikings, Black Axe, and Eiye among other fraternities. Conflict management mechanisms included negotiation and appeasement between parties. Unresolved cases were referred to the elders’ council, Ogwedion, where defaulting parties were sanctioned with traditional fines: Odegbeˋn’ekpetin. Sand mining in Evbuobanosa, Edo State is structured on positional elite-artisanal working class relational-platform, accommodated by traditional arrangements and legal-rational permits. Its conflict management mechanisms were based on traditional institutions. Government needs to implement sustainable mining regulations to minimise land degradation.